Development of Growth Pole Areas through Blue Economy-Based Fisheries Sector in Gunungkidul Regency - Efendi, Lukman; Bhinadi, Ardito (AIBPM Publisher, 2023)
Poverty is still a crucial phenomenon that must be overcome in Gunungkidul Regency. The aim of this research is to plan the development of the fisheries sector as an effort to reduce poverty. The analysis techniques used in this research are Shift Share analysis, Location Quotient (LQ), Klassen Typology, Scalogram analysis, and supported by literature studies. The results showed that the fisheries sector is a potential sector to be developed. The sub-sector that becomes the leading sector in the fisheries sector is marine fisheries.Then,the sub-sector of inland water, brackish water pond, and freshwater pond becomes a potential sub-sector. Meanwhile, cages and floating cage net are the underdeveloped sub-sector in the fisheries sector. Each district has different potential in the fisheries sector. Girisubo District can be developed as a production center. Meanwhile, Wonosari District can be developed as a processing industry center. In its management, a blue economy concept approach is recommended in this research.